Penerapan Literasi Informasi di Perpustakaan SMK Negeri 2 Pariaman - Putri, Nadia Edmi; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractThe purpose of this study were to (1) describe ability information literacy visitors in SMK Negeri 2 Pariaman’s library, (2) describe application of information literacy in library SMK Negeri 2 Pariaman. Collecting was done interview and observation. Analyzing data is done descriptively. Based on data analysis, it was concluded that information literacy ability of visitors in SMK Negeri 2 Pariaman’s library is very less, it can be seem from some ability as follows: (1) students have formulated the problem before looking for information, (2) students are more likely to access information from the internet, (3) students are still lacking in the ability to evaluate information and sources critically, (4) students are still lacking in the ability to process information into a new knowledge, (5) students have not specified the source of information used. The application of information literacy can be done in SMK Negeri 2 Pariaman’s libarary that is by user education and reading reward.Keyword: literacy, information, library